2019
DOI: 10.3390/nano9010114
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Preparation and Regulation of Pyrrole Structure Nano-Pigment Based on Biomimetic Membrane

Abstract: Microbial pigments, regarded as the most potential biomass pigments, have lately attracted increasing attention in textile dyeing due to their sustainability and cleaner production. The pyrrole structure microbial pigment, called prodigiosin, recently have become a research hotspot for its bright colors and antibacterial function. However, in most case the extraction and preparation are time-consuming and expensive processes since these kinds of microbial pigments are intracellular metabolites. In order to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…KH-95 [ 206 ], and S. marcescens SMDR [ 207 ] have been studied by adsorption to the materials with hydrophobic surfaces of polyurethane [ 188 ], internal adsorbent using acidified methanol and phase separation [ 206 ], and macroporous polymeric adsorption resin of Diaion HP-20 resins [ 207 ]. The transmembrane transport of PG producing S. marcescens ATCC 8100 and the permeability barrier of the cell membrane were studied by using a model membrane platform with a planar lipid bilayer [ 151 ]. The results showed that the mass transfer of the intracellular PG was affected by its size and surface electrical properties and therefore could be modulated by physical and chemical methods [ 151 ].…”
Section: Production Of Pgsmentioning
confidence: 99%
See 3 more Smart Citations
“…KH-95 [ 206 ], and S. marcescens SMDR [ 207 ] have been studied by adsorption to the materials with hydrophobic surfaces of polyurethane [ 188 ], internal adsorbent using acidified methanol and phase separation [ 206 ], and macroporous polymeric adsorption resin of Diaion HP-20 resins [ 207 ]. The transmembrane transport of PG producing S. marcescens ATCC 8100 and the permeability barrier of the cell membrane were studied by using a model membrane platform with a planar lipid bilayer [ 151 ]. The results showed that the mass transfer of the intracellular PG was affected by its size and surface electrical properties and therefore could be modulated by physical and chemical methods [ 151 ].…”
Section: Production Of Pgsmentioning
confidence: 99%
“…The transmembrane transport of PG producing S. marcescens ATCC 8100 and the permeability barrier of the cell membrane were studied by using a model membrane platform with a planar lipid bilayer [ 151 ]. The results showed that the mass transfer of the intracellular PG was affected by its size and surface electrical properties and therefore could be modulated by physical and chemical methods [ 151 ]. The immobilization strategy to increase PG production was investigated by Chen et al [ 172 ].…”
Section: Production Of Pgsmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple incubation method allowed 3.9% loading of LAGs by varying the composition of a methanolacetic acid solvent system, temperature, incubation time and agitation rate. The solvent system had a key role in PG loading as it was shown to promote permeabilization of the bacterial phospholipid bilayer 37,38 and protonation of PG 39,40 . This would enhance PG binding to the negatively charged LAG membrane via strong electrostatic interaction PG loading which was con rmed by digital and microscopic imaging (Fig.…”
Section: Discussionmentioning
confidence: 99%